(untitled) (Journal of Fiber Bioengineering and Informatics, 2025)
This work realises the total parametric design of the insole through the topological structural design of the lattice units, which helps to meet the pressure requirements of different locations and increase the comfort and personalisation of insoles. Prior research has primarily concentrated on creating planar porous structures and basic geometric insole structures; intricate three-dimensional lattice structure optimisation has been systematically neglected. To close this gap, the research examines three common porous lattice structural units for analysis: equilateral triangular, square, and hexagonal units. It does this by using 3D printing technology to produce customised insoles. In addition, variance analysis is carried out, and the orthogonal experimental design method is used to examine the significant impact of structural design factors on the compressive performance of the porous lattice structure. The lattice’s structural neutral size, unit size, and rod diameter are chosen to influence the elastic modulus. With a 22% reduction in maximum plantar pressure and an 18% reduction in average pressure compared to the uniform solid structure, research reveals a considerable improvement in plantar pressure distribution with the lattice insole structure created in this study. In the meantime, the porous lattice structure’s overall weight is 15% less than that of the solid structure, which successfully reduces the insole’s burden while still fulfilling the standards for mechanical performance. This study offers a fresh technological perspective on creating customised, comfortable insoles.